Access to Thrombolysis for Non-Resident and Resident Stroke Patients—A Registry-Based Comparative Study from Berlin - Schlemm, Ludwig; Turc, Guillaume; Audebert, Heinrich J.; Ebinger, Martin (Frontiers in Neurology, 2017)
Objectives: Stroke can happen to people away from home. It is unknown whether nonresident and resident stroke patients have equal access to thrombolysis. Materials and Methods: Consecutive patients cared for by the Stroke Emergency Mobile (STEMO) between 2011 and 2016 after prompting suspicion of acute stroke during the emergency call were included in our registry. Patients were categorized as residents or nonresidents based on their main address. Clinical characteristics, thrombolysis rates, and time intervals from symptom onset/last seen well to alarm and to thrombolysis were compared between groups adjusting for age, pre-stroke modified Rankin Scale (mRS) score and National Institutes of Health Stroke Scale (NIHSS) score. Results: Of 4254 patients for whom a stroke dispatch was activated, 2451 had ischemic or hemorrhagic strokes, including 73 nonresidents. Nonresident stroke patients were younger (median 69.4 vs. 76.6 years, p<0.001), had less pre-stroke disability (mRS>=2: 17.8% vs. 47.5%, p<0.001) and less severe strokes (median NIHSS 4 vs. 5, p=0.02). Thrombolysis rates were higher in nonresidents (30.9% vs. 22.0% of ischemic stroke patients, p=0.04) and emergency calls were made faster (symptom onset/last-seen-well-to-alarm time 35 vs. 144 min, p=0.04). A lower proportion of nonresidents had unknown time of symptom onset (21.9% vs. 46.4%, p<0.001). For patients with known time of symptom onset, thrombolysis rates and prehospital delays were similar among nonresidents and residents. Conclusion: In this study, nonresident stroke patients had higher rates of thrombolysis than residents. This may be explained by a lower proportion of patients with unknown time of symptom onset.